Alogliptin – a new DPP‐4 inhibitor for type 2 diabetes. Issue 22 (19th November 2014) - Chaplin, Steve; Farooqi, Azhar
<x xml:space="preserve">Abstract</x> Alogliptin (Vipidia), the latest DPP‐4 inhibitor, is licensed as second‐line therapy in patients with type 2 diabetes mellitus. Steve Chaplin presents the data relating to its efficacy and adverse events and Azhar Farooqi outlines its place in therapy.